Numerical Simulation of Flow over Bionic Airfoil - Lishu Hao; Yongwei Gao; Binbin Wei; Ke Song (International Journal of Aerospace Engineering)
In this study, the aerodynamic performance of bionic airfoil was numerically studied by CFD method. The bionic airfoil was represented by the combination of airfoil and a small trailing edge flap. A variety of configurations were calculated to study the effect of flap parameters, such as the flap angle, position, and shape, on the bionic airfoil aerodynamic characteristics based on two layouts which were that (1) there was a tiny gap between the airfoil and the flap and (2) there was no gap between the two. The results showed that the flap angle and position had significant effects on the aerodynamic performance of the airfoil with the two layouts. Compared with the clean airfoil, the maximum lift coefficients of the first layout and the second layout could be increased by 10.9% and 7.9%, respectively. And the effective angle of attack (AoA) range for improving the lift-to-drag ratio could reach 7°. The flap shape also affected the airfoil aerodynamic characteristics, and the flap with the sinusoid curve shape showed ideal performance.